Polski rynek obligacji samorządowych na tle rynków zagranicznych - Antkiewicz, Sławomir (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Municipial bonds are a dominant way of getting funds in the United States, where they have been existing for over a hundred years. Also in European countries those securities have been more and more popular. Polish market of municipial bonds has been developing in a dynamic way. The number and the value of new floats have been increasing. But among buyers banks are prevailing, therefore secondary market cannot develop considerably. But public floats, that are planned, can effect development of the market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 500-506